Toxicological and demographic profiles of phencyclidine-impaired driving cases in Houston: updates from the 2019 to 2023 data - Lee, Dayong; Corral, Salvador R; Duvall, Cassandra; Stout, Peter (Journal of analytical toxicology, 2025)
Phencyclidine (PCP) is a dissociative anesthetic harmful to road traffic safety as the drug may impair driving performance by inducing adverse effects such as sedation, ataxia, agitation, disorientation, and confusion. Houston Forensic Science Center previously reported toxicological and demographic characteristics of PCP-impaired driving cases in Houston from 2013 to 2018 and presently reports the 2019-23 cases. The blood samples collected from suspect drivers were analyzed for alcohol and drugs and those positive for PCP at the reporting limit of 5 ng/mL were included in the study (n = 1375). The drivers had the median (mean, range) PCP concentration of 45 (49, 5-170) ng/mL and were mostly males (77%) and black (89%) with the mean age of 40 years. More than half of the drivers (59%) were polydrug users with cannabinoids being the most frequently detected (39%), followed by cocaine/metabolites (15%) and ethanol (10%). Compared to our previous findings and other studies, the PCP concentration distributions and concurrent drug profiles of the drivers were remarkably consistent despite multiple changes in the drug market over the years; their demographics also remained comparable except for the mean age, which continued to increase. Continual surveillance of PCP-impaired driving cases is important to identify risk groups and aid in reducing this hazardous driving behavior, so prevalent and persistent in the city of Houston.